Tradició i innovació en la selecció de l'auxiliar de perfet a Curial e Güelfa. - MASSANELL I MESSALLES, MAR (Scripta)
One of the characteristics of Old Catalan that has not been preserved, except for some dialectal remains, is double auxiliary of perfect tenses, which were built with haver 'have' or ésser 'be' (e.g. ha parlat vs. és arribat). Haver occurred in transitive and agentive intransitive constructions, while ésser was used in statives, eventives, resultatives of change of state and change of location, pronominal intransitives, direct reflexives and passives. Although the substitution of ésser for haver is a process developed mainly during Modern Age and culminated in contemporary times, signs of it can already be detected in Medieval Catalan. In this paper, starting from the extraction and classification of perfects in Curial e Güelfa, we identify the samples in which haver occurs instead of ésser, we analyze the factors that may have favored it and we relate them to the entry routes of haver indicated in previous works. We conclude that Curial e Güelfa firmly maintains double auxiliary, innovation being practically restricted to the relative impersonal constructions with romandre 'remain', sobrar 'be left over', venir 'come', esdevenir 'become' and succeir 'happen', which contain a dative experiencer as a logical subject.